Welfare Dynamics and Employment: Heterogeneous Paths Through Means-tested Basic Income in Germany - Bruckmeier, K., Lietzmann, T., and Saile, A. (Journal of Social Policy)
This study contributes to the international literature on welfare dynamics, by providing a differentiated picture of paths through the means-tested Basic Income for recipients who are capable of working, after the reorganisation of the basic income system in Germany in 2005. We analyse the employment and benefit trajectories of individuals who became recipients for the first time between 2007 and 2009 by methods of sequence and cluster analysis based on representative administrative individual data. We find a significant polarisation between long-term recipients and those with an early exit from benefit receipt via full-time employment. One in three new recipients remains in benefit receipt for the next years and shows almost no employment activities. Approximately 23 percent leave benefit receipt quickly and work in full-time employment. Several other different paths exist between these two poles. These heterogeneous trajectories should be characteristic for broad basic income systems and require a variety of policies that in part are beyond labour market policies. - Reproduced
Keywords: Employment - Germany, Income - Germany